2009
DOI: 10.1088/0004-637x/691/2/1380
|View full text |Cite
|
Sign up to set email alerts
|

SN 2001em: NOT SO FAST

Abstract: SN 2001em is a peculiar supernova, originally classified as Type Ib/c. About two years after the SN it was detected in the radio, showing a rising radio flux with an optically thin spectral slope, and it also displayed a large X-ray luminosity (∼ 10 41 erg s −1 ). Thus it was suspected to harbor a decelerating (by then, mildly) relativistic jet pointing away from us. About 3 years after its discovery the optical spectrum of SN 2001em showed a broad Hα line, and it was therefore reclassified as Type IIn. Here w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…In Figure 2, we plot the size against the age for SN 2008D, and compare it to those measured for GRB 030329, and for SN 2001em, another Type Ib/c SN that was a candidate for an off-axis GRB but was shown to have only SN expansion velocities, as well as for SN 1993J, a typical Type IIb SN. We note that a more recent measurement of SN 2001em by Schinzel et al (2008) further limits the expansion velocity of SN 2001em, and an additional 1.6 GHz measurement by Paragi et al (2005) is consistent with the plotted values. Our (2σ ) upper limits on the extent of SN 2008D are considerably lower than the sizes measured for GRB 030329, with SN 2008D showing subluminal expansion, while GRB 030329 shows superluminal expansion till t 300 days.…”
Section: Discussionsupporting
confidence: 87%
“…In Figure 2, we plot the size against the age for SN 2008D, and compare it to those measured for GRB 030329, and for SN 2001em, another Type Ib/c SN that was a candidate for an off-axis GRB but was shown to have only SN expansion velocities, as well as for SN 1993J, a typical Type IIb SN. We note that a more recent measurement of SN 2001em by Schinzel et al (2008) further limits the expansion velocity of SN 2001em, and an additional 1.6 GHz measurement by Paragi et al (2005) is consistent with the plotted values. Our (2σ ) upper limits on the extent of SN 2008D are considerably lower than the sizes measured for GRB 030329, with SN 2008D showing subluminal expansion, while GRB 030329 shows superluminal expansion till t 300 days.…”
Section: Discussionsupporting
confidence: 87%
“…SN 1994W (Chugai et al 2004;Dessart et al 2009). Several observed SNe have a CSM density that seemed to increase with distance from the progenitor: SN 2008iy (Miller et al 2010), SN 1996cr (Bauer et al 2008), SN 2001em (Chugai & Chevalier 2006Schinzel et al 2009), and SN 2011ja (Chakraborti et al 2013), suggesting that at least at certain radii, the CSM may be better modeled as a CSM shell rather than a smooth r −2 wind. Also, some of the ultra-luminous X-ray (ULX) sources with luminosities up to ∼ 10 41 erg s −1 , especially the ones with a thermal spectrum and slow variability, may be due to supernova interacting with massive cirumstellar shells (Swartz et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although it was originally thought that SN 2001em may harbor a bipolar relativistic off-axis jet that had decelerated to mildly relativistic velocities (Granot & Ramirez-Ruiz 2004), later observations with very long baseline interferometry ruled this model out by demonstrating that the expansion velocity of the supernova was below 6000 km s −1 and that the supernova was therefore not driven by a relativistic jet (Bietenholz & Bartel 2005Schinzel et al 2009). Chugai & Chevalier (2006) found that the multi-wavelength properties of SN 2001em could be modeled in a scenario in which non-relativistic ejecta from the supernova explosion collided with a dense and massive (∼ 3 M ⊙ ) circumstellar shell at a distance of ∼ 7 × 10 16 cm from the star.…”
Section: Previous Examples Of Delayed Interactionmentioning
confidence: 99%